Second Five Year Plan of West Bengal Annual Plan 1958-59 - Planning Commission (Planning Commission, 1958)
One of the features of the Second Five Year Plan is its flexibility in the sense that the plan has to be broken up into annual plans. the Second Five - Year Plan is to be treated as a broad framework within which programmes for each year have to be worked out in detail. Such an approach is expected to give an opportunity for making adjustments in the light of new developments. On the basis of this decision the State Government have been preparing annual plans within the framework of its Second Five Year Plan. The procedure adopted is something like this. Each department prepares the detailed estimates and programme for a particular year in respect of the Head with which it is concerned. It also prepares a progress report in respect of the programme of the previous year. These estimates and programmes are then compiled and integrated into a draft plan for the State.
Government of West Bengal